Radio frequency reflection characteristics of shale fragmentation subject to uniaxial compression. (June 2019) - Ren, Hongji; Yin, Aijun; Yao, Wenquan; Wang, Jian; Zhou, Junping
Highlights: Radiofrequency reflection features under shale fragmentation are studied. AE and RF sensors are utilized to monitor the fragmentation process of shale. AE and RF reflection features have similar trends under fragmentation. Abstract: In order to realize the safe exploitation of shale gas, extensive efforts have been focused on investigating the correlations between shale fragmentation evolution and the variations of mechanical properties, thermal properties and acoustical properties. Current shale fragmentation monitoring approaches are generally limited by poor real-time performance, inflexibility, and susceptible to interference. In this paper, the radiofrequency (RF) reflection characteristics for shale fragmentation subject to uniaxial compression are investigated. A simulation model is developed to assess the feasibility of RF based shale damage evaluation. A shale fragmentation experiment equipped with acoustic emission (AE) system, mechanical testing system, and the proposed RF reflection monitoring system is conducted and multi-physics parameters are recorded. A customized RF sensor with a frequency of 150 MHz is employed to acquire RF reflection coefficient. Experiment results indicate that AE activities and RF reflection features have similar trends under the evolution of shale damage. Despite of fluctuations, the proposed RF method is able to represent the shale fragmentation process. The findings in this paper can be applied on RF based active shale fragmentation monitoring to prevent borehole accidents.